LINGUISTIC THEORY INTEGRATED WITH LANGUAGE TEACHING AND THE PHILOLOGICAL APPROACH IN PEDAGOGICAL PRACTICE (Scientific journal of the Fergana State University, 2025)
The integration of linguistic theory into language teaching is increasingly recognized as a vital component for enhancing pedagogical practices. This article, "Integrating Linguistic Theory into Language Teaching: A Philological Approach to Pedagogical Practice," explores how foundational principles of linguistic theory can be applied to improve language instruction. By adopting a philological perspective, which emphasizes historical and comparative approaches, this study reviews the impact of key linguistic theories—generative grammar, sociolinguistics, and cognitive linguistics—on teaching methodologies. The study employs a multi-phase research methodology, including theoretical framework development, empirical data collection, and pedagogical analysis, to evaluate how these theories are implemented in language classrooms. The comparative analysis reveals varying degrees of theory adoption based on educational context and teacher expertise, with higher education settings showing greater use of cognitive and philological approaches. This article provides a comprehensive overview of how theoretical insights can inform effective teaching strategies and offers recommendations for educators to better integrate linguistic theory into their practices.